Morphology of traumatic cataract: does it play a role in final visual outcome? - Mehul A Shah; Shreya M Shah; Shashank B Shah; Chintan G Patel; Utsav A Patel (BMJ Open, 2011)
Aim To study the morphology of traumatic cataract as an important predictor for final visual outcome after treatment of traumatic cataracts.Setting Tertiary eye care centre in Dahod at the trijunction of Gujarat, Madhya Pradesh, and Rajasthan states in central western India.Methods This was a prospective observational cohort study among all patients presenting at the hospital with traumatic cataracts between January 2003 and December 2009. All information regarding demographic and ocular trauma was collected on a pretested World Eye Trauma Registry form for both the first visit and follow-up. In particular, the authors collected specific information about the morphology of traumatic cataracts; the surgical technique was determined accordingly. Data were entered and analysed with regard to the relationship between type of trauma and resulting injury, results achieved with particular surgical techniques, and the relationship between morphology and final visual outcome.Outcome measures Final visual outcome.Results Traumatic cataracts of different morphologies showed significant differences in the final visual outcome (χ2 test, p=0.014).Conclusion The morphology of traumatic cataract plays an important role in the final visual outcome.